Changes in the electrocardiographic response to exercise in healthy women. Issue 6 (December 1990) - Deckers, J W; Vinke, R V; Vos, J R; Simoons, M L
Abstract : Changes in the P wave, QRS complex, ST segment, and T wave during and after maximal exercise were quantitatively analysed in 116 healthy women with a mean age of 39. The corrected orthogonal Frank lead electrocardiogram was continuously recorded and computer processed during bicycle ergometry. With exercise, maximal spatial P wave vectors shifted downward. The Q wave amplitude became more negative and the R wave amplitude diminished considerably in leads X and Y: the S wave amplitude decreased only slightly in these leads. The QRS vectors shifted towards right and posteriorly during exertion and a further shift in the same direction was seen in the recovery period. The ST segment amplitude 60 ms after the J point decreased with exertion and became negative at heart rates above 140 beats per minute, in particular in lead Y. ST segment depression increased with age. The T wave amplitude decreased during exercise and increased sharply in the recovery period. Though mean R wave amplitude in leads X and Y became more negative with exercise, this response was unpredictable in individual women. The exercise induced changes in QRS vectors in women resembled those described in men. Changes in the amplitude of the R wave should not be used for the diagnosis of coronary disease in women. ST segment depression was more pronounced in the inferiorly oriented lead Y than in lead X but it was unrelated to changes in the QRS vectors in these leads.